THE EFFECTIVENESS OF INTRA-OPERATIVE CHOLANGIOGRAM (IOC) IN DETERMINING RESIDUAL CBD STONES. DOES IT AFFECT HOW INDIVIDUALS WITH ACUTE BILIARY PANCREATITIS ARE TREATED? (The Research of Medical Science Review, 2025)
Background: In the settings of acute pancreatitis associated with gallstones, the use of standard management calls for cholecystectomy once the initial symptoms have abated. An intraoperative cholangiography is performed with laparoscopic cholecystectomy to identify stones in CBD and biliary tree anatomy. Little evidence is available on the use of intraoperative cholangiography (IOC) in patients with Gallstone Pancreatitis. While performing this study, the main aim was to determine the role of IOC in detecting residual common bile duct (CBD) stones in patients undergoing cholecystectomy for acute gallstone pancreatitis (GP). Methods: This retrospective observational study was conducted after obtaining approval from the hospital administration. The hospital medical records of all patients who underwent cholecystectomy and IOC during the same admission period at the Department of Surgery, Liaquat National Hospital, and Medical College, from July 2015 to June 2018 were reviewed to assess the frequency of CBD stones after an acute event of GP. Results: After a thorough evaluation of 345 patients, 66 patients satisfied our inclusion criteria, with a mean age of 47+14 years. More than half of the patients were females (n=40, 60.6%). All patients had undergone successful IOC. Out of 66, 11(16.7%) were found to have CBD stones on IOC, and postoperative ERCP was done for all 11 patients, which revealed CBD stones. The frequency of CBD stones was 10.6% (7/66). 4 patients were not included in determining frequency as they had raised biochemistry levels (serum liver function tests). Conclusion: The current study revealed that people with gallstone pancreatitis are more likely to have CBD stones on IOC than those with just symptomatic gallstones without pancreatitis. So, the IOC can alter postoperative management and should be considered in all patients undergoing cholecystectomy for gallstone